Epigenetically altered macrophages promote development of diabetes-associated atherosclerosis - Huang, Dong; Gao, Wei; Zhong, Xin; Wu, Hongxian; Zhou, You; Ma, Yuanji; Qian, Juying; Ge, Junbo (Frontiers in Immunology, 2023)
Background: Atherosclerosis (AS) risk is elevated in diabetic patients, but the underlying mechanism such as involvement of epigenetic control of foam macrophages remains unclear. We have previously shown the importance of immune regulation on endothelial cells to AS development in diabetes. In this study, we examined the hypothesis that diabetes may promote AS through modification of the epigenetic status of macrophages. Methods: We employed the Laser Capture Microdissection (LCM) method to evaluate the expression levels of key epigenetic regulators in both endothelial cells and macrophages at the AS lesions of patients. We then assessed the correlation between the significantly altered epigenetic regulator and serum levels of high-density Lipoprotein (HDL), low-density Lipoprotein (LDL), and triglycerides (TRIG) in patients. In vitro, the effects of high glucose on glucose utilization, lactate production, succinate levels, oxygen consumption and polarization in either undifferentiated or differentiated bone marrow-derived macrophages (BMDMs) were analyzed. The effects of depleting this significantly altered epigenetic regulator in macrophages on AS development were assessed in AS-prone diabetic mice. Results: Histone deacetylase 3 (HDAC3) was identified as the most significantly altered epigenetic regulator in macrophages from the AS lesions in human diabetic patients. The levels of HDAC3 positively correlated with high serum LDL and TRIG, as well as low serum HDL. High glucose significantly increased glucose utilization, lactate production, succinate levels and oxygen consumption in cultured macrophages, and induced proinflammatory M1-like polarization. Macrophage depletion of HDAC3 significantly attenuated AS severity in AS-prone diabetic mice. Conclusion: Epigenetically altered macrophages promote development of diabetes-associated AS, which could be prevented through HDAC3 depletion.